Stenting of vertical vein in an infant with obstructed supracardiac total anomalous pulmonary venous drainage - W K Lim; M C Leong; H Samion (Wolters Kluwer Medknow Publications, 2016)
A 1.7 kg infant with obstructed supracardiac total anomalous pulmonary venous drainage (TAPVD) presented with severe pulmonary hypertension secondary to vertical vein obstruction. The child, in addition, had a large omphalocele that was being managed conservatively. The combination of low weight, unoperated omphalocele, and severe pulmonary hypertension made corrective cardiac surgery very high-risk. Therefore, transcatheter stenting of the stenotic vertical vein, as a bridge to corrective surgery was carried out. The procedure was carried out through the right internal jugular vein (RIJ). The stenotic segment of the vertical vein was stented using a coronary stent. After procedure, the child was discharged well to the referred hospital for weight gain and spontaneous epithelialization of the omphalocele. Stenting of the vertical vein through the internal jugular vein can be considered in very small neonates as a bridge to repair obstructed supracardiac total anomalous venous drainage.